The Development of Multicultural Counselling Competencies (MCC) Training Module Based on MCC Matrix Model by Sue et al. (1992) - Azad Athahiri Anuar; Norsayyidatina Che Rozubi; Haslee Sharil Abdullah (Malaysian Online Journal of Educational Technology (MOJET), 2024)
The aims of this study were to develop and validate a MCC training module for trainee counselor based on MCC matrix model by Sue et al. (1992). This module encompassed five sub modules and 11 activities developed along the concepts and components of the MCC matrix model developed by Sue, Arredondo dan McDavis (1992). The design method used in this study involved a descriptive approach involving expert judgment. In addition, literature review was used to examine the need for developing of MCC training modules and to justify usage the MCC matrix model by Sue et al. (1992). The instruments used to determine the content validity of the module as advocated by Jamaludin (2002) is a modification from Russell (1974). The sample of the study comprised six experts in the field of counseling and psychology. A statistical software was used to analyze the descriptive statistics of the collected data which revealed promising results. The values computed for the content validity were high, ranging from 73.3% to 86.6%. These findings reinforce the MCC matrix model by Sue et al. (1992) in the design of MCC training module for counseling practitioners in Malaysia. Implications of the findings are discussed.